Biennial review of health care management - Blair, John D.; Fottler, Myron D.; Savage, Grant T. (Grant Theodore), 1954- (Bingley, U.K. : Emerald, 2011)
This is the second biennial volume reviewing the state-of-the-art on a wide variety of micro and macro health care management topics in the popular'Advances in Health Care Management' series. It proudly showcases reviews of both empirical and conceptual research in specific areas of health care management, including topics in three basic areas: reviews of empirical and conceptual research on health care industry-specific topics, e.g., role of physicians; reviews of empirical and conceptual research on different types of health care organizations focusing on issues specific to such organizations or their segments of the health care industry, e.g., hospitals, managed care organizations; and, reviews of empirical and conceptual research on health care organizations focusing on topics or variables which cover various sub-disciplines of management, e.g., organizational change or entrepreneurial opportunity recognition. New and established scholars discuss such topics within their expert area of research, as well as emerging themes and divergent views, giving their unique perspective on the directions that will help build theory and improve the practice of health care management.
Context-specific and/or context-free challenges and opportunities in writing scholarly reviews in health care management : a conceptual note / John D. Blair -- Organizing for performance : what does the empirical literature reveal about the influence of organizational factors on hospital financial performance? / Harry D. Holt, Jonathan Clark, Jami DelliFraine, Diane Brannon -- Exploring the relationship between private equity ownership and nursing home performance : a review / Rohit Pradhan, Robert Weech-Maldonado -- Hospital handoffs as multifunctional situated routines : implications for researchers and administrators / Brian Hilligoss, Michael D. Cohen -- Transforming the dominant logic of hospitals / Kenneth R. White, Steven Thompson, John R. Griffith -- Navigating patient navigation : crossing health services research and clinical boundaries / Victoria A. Parker, Christy Harris Lemak -- Determinants of health insurance coverage rates for young adults : an analytical literature review / John Cantiello, Myron D. Fottler, Dawn Oetjen, Ning Jackie Zhang -- Evidence-based decision making in health care settings : from theory to practice / Melanie Kazman Kohn, Whitney Berta, Ann Langley, David Davis -- Text messaging in health care : a systematic review of impact studies / Valerie A. Yeager, Nir Menachemi.
Keywords: Health services administration